With or against Each Other? The Influence of a Virtual Agent's (Non)cooperative Behavior on User's Cooperation Behavior in the Prisoners' Dilemma. (20th September 2018) - Straßmann, Carolin; Rosenthal-von der Pütten, Astrid M.; Krämer, Nicole C.
Abstract : Most applications for virtual agents require the user to cooperate. Thus, it is helpful to investigate different strategies for virtual agents to evoke the user's cooperation. In the present work ( N = 80), we experimentally tested the influence of an agent's (non)cooperative nonverbal behavior and actual decision-making behavior on user's cooperation in the Prisoners' Dilemma considering different age groups (students and seniors). Therefore, we used a 2 (nonverbal behavior) x 2 (age group) between-subjects design in Wizard-of-Oz study. Results show age differences with seniors cooperating more often than students do. The nonverbal behavior had no effect on the users' willingness to cooperate nor on the evaluation of the agent's cooperativeness. However, the agent's decision-making behavior in the game influenced the users' willingness to cooperate. In summary, the nonverbal behavior seemed to be too subtle, while the actions of the agent were important in terms of cooperation.